THE ROLE OF INNOVATIVE TECHNOLOGIES IN FOREIGN LANGUAGE TEACHING - Aliboeva Nilufar Makhamatali kizi; Mirzamatova Muslimaxon Botirjon qizi (Researchparks Publishing, 2023)
This article discusses the role of innovative technologies in foreign language teaching, the use of effective methods in the classroom and their role in improving the quality of education.